Where Do Born Globals Come from? A Neoconfigurational Institutional Theory - Fainshmidt, Stav; Smith, Adam W.; Aguilera, Ruth V. (Organization Science, 2022)
Born globals, recently established firms that obtain a substantial share of their revenue from foreign markets, can help strengthen countries’ economic vitality and increase innovation levels. The extent of born global formation varies considerably across countries, yet it is unclear why this is the case. Drawing on the neoconfigurational institutional perspective, we develop a typology of institutional contexts associated with high born global formation rates. We posit that high rates of born global formation occur where institutional features favorable to border-spanning activities complement institutional features conducive to entrepreneurial activity, thus forming an institutional configuration that enables, equips, and motivates more societal members to launch born globals. Accordingly, we hypothesize a primary institutional configuration where international transaction facilitators, entrepreneurial educational capital, and entrepreneurial norms combine to propel born global formation. Further, we draw on the internationalization literature to propose two alternative types of institutional configurations conducive to born global formation. These two types provide functional substitutes for the primary type and are distinctly propelled by (1) escapism from low-quality public governance institutions or (2) immigrant entrepreneurship. Fuzzy-set qualitative comparative analysis on data from 66 countries supports our typology and illustrates why born global activity may thrive even in contexts with institutional weaknesses. Our study develops a neoconfigurational model to advance a holistic understanding of the born global phenomenon’s theoretical drivers, contributing to research on comparative capitalism and international entrepreneurship.